HUBUNGAN ANTARA PEMAHAMAN DEMOKRASI DENGAN PARTISIPASI POLITIK PADA PILKADES 2021 MASYARAKAT DESA JAYA SAKTI KECAMATAN KAYAN HILIR KABUPATEN SINTANG - Mardawani Mardawani; Sapto Purnomo; Jemi Febriani (JURNAL PEKAN : Jurnal Pendidikan Kewarganegaraan, 2023)
The purpose of this study was to find out the relationship between understanding democracy and political participation in the 2021 Pilkades for the people of Jaya Sakti Village, Kayan Hilir District, Sintang Regency. This research uses quantitative methods in the form of interactive relationship study research. The population in this study were 615 permanent voters and from the results of calculations using the Yamane formula, a sample of 85 respondents was obtained. Data collection techniques and tools using questionnaires and documentation. Data processing techniques include normality test, simple linear regression analysis, correlation analysis, and t test. The results of the study show, 1) the people's understanding of democracy is in a fairly good range by looking at the close average valuean average of 163,16% and a minimum score of 143, 2) political participation in the 2021 village head election, the community is in the fairly good category with an average score of 174,46% and a minimum score of 154. The product moment correlation test shows a correlation value of 0,594 and the level of relationship is classified as currently. The significance test shows the value of tcount 6,732 > ttable 1,988 then Ho is rejected and Ha is accepted. Furthermore, there is a significant relationship between understanding democracy and political participation in the 2021 Pilkades for the people of Jaya Sakti Village, Kayan Hilir District, Sintang Regency.  Keywords: Democracy, Political Participation in Pilkades